2022
DOI: 10.1111/cfs.12980
|View full text |Cite
|
Sign up to set email alerts
|

The concept of family: Perspectives of Spanish young people in foster care

Abstract: This article employs concepts from family sociology to explore how 'family' is conceptualised in 14 life narratives of young people in foster care in Spain. The article draws on a multi-method approach with young people who are in long-term nonkinship foster care. Seven girls and seven boys aged 10 to 22 took part in the study.The empirical material reveals an interplay between biological preference and foster family affective practices in young people's narratives, illuminating a struggle to make sense of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Both the foster children and the foster parents in Study 3 relate to what a 'real' family is assumed to be, and they often try to build something that is similar to a 'real' family, or different, but still valuable. This is consistent with previous foster care research that has shown the importance of inclusion in the family and how both parties work with these issues (Christiansen et al, 2013;Ie, 2022;Schofield & Beek, 2005;Storer et al, 2014). Most of the children and foster parents like each other but struggle with concepts such as 'family' and with defining their relationship.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Both the foster children and the foster parents in Study 3 relate to what a 'real' family is assumed to be, and they often try to build something that is similar to a 'real' family, or different, but still valuable. This is consistent with previous foster care research that has shown the importance of inclusion in the family and how both parties work with these issues (Christiansen et al, 2013;Ie, 2022;Schofield & Beek, 2005;Storer et al, 2014). Most of the children and foster parents like each other but struggle with concepts such as 'family' and with defining their relationship.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Qualitative studies have, for example, focused on children's and young people's experiences of foster care, parents' experiences of having their child in foster care or foster parents experiences of being foster parents (e. g. Andersson, 2016;Christiansen et al, 2013;Höjer, 2009;Ie, 2022;Join-Lambert & Reimer, 2022). Other qualitative studies aim to deepen the understanding of processes in foster families and in the context of foster care (e. g. Rostill-Brookes et al, 2011;Sprecher et al, 2022;Wissö et al, 2019).…”
Section: Foster Care Research Findingsmentioning
confidence: 99%
“…Initially, this study set out to explore how family is perceived in long‐term non‐kinship foster care. However, many participants had very limited or no contact with their fathers, and their reflections concerning their mothers were more prominent in the data (see Ie, 2022). We thus chose to explore these perceptions in a more detailed manner by analysing patterns in the data addressing their relationship with their birth mothers.…”
Section: Methodsmentioning
confidence: 99%
“…As Landes and Settersten (2019) explain, linked lives can also bound human agency. In instances where individuals are dependent on support or care from othersa characteristic of the human condition that is universal but more obvious in familiarised welfare states and particularly in the lives of many foster children and young peoplethe ability to engage in agentic family relationships is directly related to the quality of these relationships (Ie, 2022;Ie & Ellingsen, 2023). Within the family context, researchers have explored the interdependence of individuals' agency and the contexts of shared meanings (Boden-Stuart et al, 2021;Lee, 2019;Finch & Mason, 1993).…”
Section: The Agentic Child As a Relational Being Of Interpersonal Int...mentioning
confidence: 99%
“…Individual perceptions of family are shaped by experiences and cultural understandings. Therefore, drawings help to recognise that children and young people's construction of family in long-term foster care are socioculturally related (Ie, 2022).…”
Section: Drawingsmentioning
confidence: 99%